The effects of Germany's new minimum wage on employment and welfare dependency - Sebastian Schmitz (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2017)
In January 2015, Germany introduced a federal, statutory minimum wage of 8.50 exteuro per hour. This study evaluates the effects of this policy on regular and marginal employment and on welfare dependency. Based on county-level administrative data, this study uses the difference-in-differences technique, exploiting regional variation in the bite of the minimum wage, i.e. the county-specific share of employees paid less than 8.50 exteuro before the introduction of the minimum wage. The minimum wage had a considerable negative effect on marginal employment. There is also some indication that regular employment was slightly reduced. Concerning welfare dependency, the minimum wage reduced the number of working welfare recipients, with some indication that about one half of them left welfare receipt due to the minimum wage.
Keywords: I38; J22; J30; 330; minimum wages; welfare dependency; labor supply; Germany